2021
DOI: 10.1001/jamapsychiatry.2021.2332
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Trends in Suicidal Behavior Among US Military Veterans During the COVID-19 Pandemic

Abstract: IMPORTANCEThe COVID-19 pandemic has raised considerable concerns about increased risk for suicidal behavior among US military veterans, who already had elevated rates of suicide before the pandemic.OBJECTIVE To examine longitudinal changes in suicidal behavior from before the COVID-19 pandemic to nearly 10 months into the pandemic and identify risk factors and COVID-related variables associated with new-onset suicide ideation (SI). DESIGN, SETTING, AND PARTICIPANTS This population-based prospective cohort stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 49 publications
3
36
0
2
Order By: Relevance
“…Results of this study further indicated that prepandemic loneliness and pandemic-related social stressors were associated with an increase in psychological distress [ 15 ]. Although suicide among veterans over the course of the pandemic did not increase, low social support and worsening of social relationships were among the risk factors present for veterans who did develop new-onset suicide ideation during the pandemic [ 16 ]. Additionally, at the beginning of the pandemic, it was hypothesized that there might be a mental health crisis among older adults due in part to complications from the difficulty in adopting technologies useful during quarantine (eg, software to facilitate telehealth visits or stay connected with loved ones) and lack of contact with friends, family, and caregivers [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Results of this study further indicated that prepandemic loneliness and pandemic-related social stressors were associated with an increase in psychological distress [ 15 ]. Although suicide among veterans over the course of the pandemic did not increase, low social support and worsening of social relationships were among the risk factors present for veterans who did develop new-onset suicide ideation during the pandemic [ 16 ]. Additionally, at the beginning of the pandemic, it was hypothesized that there might be a mental health crisis among older adults due in part to complications from the difficulty in adopting technologies useful during quarantine (eg, software to facilitate telehealth visits or stay connected with loved ones) and lack of contact with friends, family, and caregivers [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Measuring the impact of COVID-19 on population mental health poses significant challenges (Patten et al 2021). While numerous studies have reported increase in psychiatric morbidity since onset of COVID-19, in particular for population levels of depression and anxiety (COVID-19 Mental Disorders Collaborators, 2021;Thorisdottir et al 2021;Santabárbara et al 2021;Fancourt et al 2021;Pierce et al 2020;Samji et al 2021), some studies have also suggested the possibility that the overall effect on population mental health was moderate (Hafstad et al 2021;Sharp et al 2021;Knudsen et al 2021;Nichter et al 2021;John et al 2020). Several of these studies suggest greater mental health issues among those diagnosed with COVID-19 and perhaps among certain population cohorts such as the youth population.…”
Section: Mental Health and Societal Impacts Of Covid-19mentioning
confidence: 99%
“…Patients with pre-existing mental disorders appeared to be at higher risk for wide-ranging mental health effects [ 5 , 6 , 7 ]. Regarding the veteran population, the results from recent studies revealed resilience to mental health problems and lower rates of suicidal ideation among US military veterans nearly 10 months into the pandemic [ 8 , 9 ]. However, these studies also showed that the prevalence of generalized anxiety disorder increased and the prevalence of major depressive disorder and post-traumatic stress disorder (PTSD) remained stable during the pandemic [ 10 ].…”
Section: Introductionmentioning
confidence: 99%